비간섭화 제어이론기반 정밀작업용 테이블의 진동억제시스템 구축에 관한 연구 - 박환철(Hwan-Cheol Park); 김영복(Young-Bok Kim); 정지현(Ji-Hyun Jeong) (동력시스템공학회지, 2021)
본 논문에서는 정밀작업용 테이블의 외란억제성능을 개선하기 위한 새로운 능동제어기법 을 제안하였다. 본 연구에서는 입력과 출력간의 전달특성이 독립적으로 나타나도록 하는 비간섭화 제어이론에 기반하여 제어기를 설계하여 하나의 입력에 대한 영향이 하나의 출력으로만 나타나도 록 시스템이 재구성된다. 따라서 독립된 각각의 시스템에 대해 제어계를 독립적으로 설계함으로써 바람직한 제어성능 및 제진성능을 달성할 수 있었다. 또한 비간섭화와 시스템의 안정성을 동시에 만족시키는 제어기 설계법을 LMI 조건으로 제시하였으며, 시뮬레이션을 통해 제안하는 기법의 유 효성을 검증하였다. This paper presents a novel method for designing a active vibration isolation system (AVIS) by noninteracting control theory. In the result, the designed system can effectively reject the impact of disturbances on high precision fabrication table. In particular, the authors provide a noninteracting control scheme to decrease and delete the interactions appeared in the controlled system dynamics such that the control performance can be improved. For designing an optimal servo system, the LMI (linear matrix inequality) approach is introduced. To verify the effectiveness of the proposed method, a simulation is performed. In the result, the vibration suppression performance is significantly improved, thereby enabling higher precision works. KCI Citation Count: 0